A hidrografia de Marechal Cândido Rondon apresentada de forma inclusiva, significativa e sustentável - Lourdes , Ivonete do Carmo de (2020)
Nowadays we have been a lot discussed about the importance of taking knowledge to the students in a meaningful and democratic way. That means, in other words, to offer Education to all without any kind of discrimination, through pedagogic actions that can get the entire scholar community’s interests. This research has the general aim of presenting the hydrography of Marechal Cândido Rondon City (MCR), in a sustainable and inclusive way for all the actors of the Educative Process. Considering this, the research of a qualitative nature and interdisciplinary characterization was accomplished in three complementary phases: the first was by mapping the Brazilian’s Inclusion through some official documents and the collection of data in The Regional Nucleon of Education of Toledo City, Paraná state. The second phase was set by a bibliographic study about the MCR’s hydrography complemented by a Case and History Study about a local family nearby the district, arroyo Marreco, which used to have a small hydroelectric usina. This example can illustrate the way the water was used that time (in the 50s), and also can demonstrate if the water exploitation followed the Water Law, the main official document that rules the correct way of using this natural source, taking in account the sustainability fundament. After the results analysis from these phases, in the final phase of the research, we develop a didactic material about the thematic of the study in a bilingual (LIBRAS and Portuguese) e-book and video form. Among the main authors, we can quote Andrade (2014), Almeida (1998) e Carvalho (1997) Pfluck (2013), Boff (1999), Dias (1992) e Loureiro (2009) to inform the relevant issues such as the Inclusion, Science, Geography, and Sustainability. As the main results, we can highlight that democratization of education is a relevant thematic which needs joining strategies from different fields. We can point that Interdisciplinary represents a good source to be explored.